An Encounter With the Other: A Thematic and Content Analysis of DMT Experiences From a Naturalistic Field Study - Michael, Pascal; Luke, David; Robinson, Oliver (Frontiers in Psychology, 2021)
Introduction:N,N-dimethyltryptamine (DMT) is an endogenous serotonergic psychedelic capable of producing radical shifts in conscious experience. Increasing trends in its use, as well as new trials administering DMT to patients, indicate the growing importance of a thorough elucidation of the qualitative content, over and above structure, which the drug occasions. This is particularly in light of the hyper-real, otherworldly, and often ontologically challenging yet potentially transformative, nature of the experience, not least encounters with apparently non-self social agents. Laboratory studies have been limited by clinical setting and lacking qualitative analyses of experiential content, while online surveys’ limitations lie in retrospective design, uncontrolled use, and both of which not guaranteeing ‘breakthrough’ experiences, i.e., producing very strong psychoactive effects. Methods: We report on the first naturalistic field study of DMT use including its qualitative analysis. Screened, healthy, anonymised and experienced DMT users were observed during their non-clinical use of the drug at home (40–75 mg inhaled). In-depth semi-structured interviews (inspired by the micro-phenomenological technique) were employed immediately after their experience. This paper reports on the thematic analysis of one major domain of the breakthrough experiences elicited, the ‘other’. Thirty-six post-DMT experience interviews with mostly Caucasian (83%) males (eight female) of average 37 years were predominantly inductively coded. Results: Invariably, profound and highly intense experiences occurred. The first overarching category comprised the encounter with other ‘beings’ (94% of reports), encompassing super-ordinate themes including the entities’ role, appearance, demeanour, communication and interaction; while the second overarching category comprised experiences of emerging into other ‘worlds’ (100% of reports), encompassing super-ordinate themes of the scene, the contents and quality of the immersive spaces. Many further mid-level themes and subthemes also illuminate the rich content of the DMT experience. Discussion: The present study provides a systematic and in-depth analysis of the nuanced content of the otherworldly encounter within the breakthrough DMT experience, as well as elaborating on the resonances both with previous DMT studies focusing on entity encounters and other types of extraordinary experiences entailing such encounters. These include the alien abduction, folkloric, shamanic and near-death experience. Putative neural mechanisms of these features of the DMT experience and its promise as a psychotherapeutic agent are discussed in light of such findings.